The External Factors of Andrea Sachs’ Personality Development - Budiarto, Budiarto; Abigail, Erika; suhendar, suhendar (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
The writer focuses on the personality development that often focuses on how an individual adapts or changes their actions and behavior based on various factors as human. The development is often represented through literature, which reflects real life conditions. This study aims to investigate the personality development and its relation to moral values represented by the main character in The Devil Wears Prada (2006). The writer uses content analysis method with qualitative approach to further analyze and interpret the data that are in the form of film scenes and dialogues. Moreover, the theory of personality development by Elizabeth Hurlock is used to guide the analysis in this research. The findings show that Andrea Sachs’ personality development is influenced by the working environment. The internal factors of Andrea’s personality are temperament, emotion, and self. Meanwhile, the external factors are physical, social, and aspiration determinants. The role of moral values in Andrea’s personality development is also discovered as the essential aspect that influences Andrea’s initial personality of being resistance to fashion, skeptical towards the work ethic in fashion industry, and indifferent to fashion industry. The external factors are the most important in the development that finally she is becoming aware of fashion sense. She values fashion positively, and works hard in Runway due to the external factors. The implication of research is to expand knowledge about transformation from Estella into Cruella based on the changes of appearance, character and the effects of the transformation due to the external factors.